Final Cut Express 2 : - Wolsky, Tom (CMP Books, 2004)
Final Cut Express 2 Editing Workshop is a classroom-in-a-book that teaches readers the art and technique of editing with Final Cut Express 2. It features a series of tutorials that cover the complete range of tasks, from installing the application to outputting. All of the necessary materials, including raw video footage and sequences, detailed instructions, and techniques taught in film schools, guide the reader to a working knowledge of Final Cut Express 2. The companion DVD includes a video introduction to Final Cut Express 2 specially designed for iMovie users, as well as tutorial media and plug-ins.